Experiential graphic design in rural tourism: A model for navigation, identification, and experience - Elif Atamaz (Journal of Rural Tourism, 2026)
Purpose - This study aims to investigate how Experiential Graphic Design (EGD) can enhance sustainable rural tourism by improving spatial communication, strengthening cultural identity, and fostering emotionally engaging visitor experiences. It introduces the Navigation–Identification–Experience (NIE) framework as a conceptual model for integrating EGD into rural tourism planning.Methodology/Design/Approach - The research draws upon theoretical foundations from Kevin Lynch’s spatial legibility, Yi-Fu Tuan’s topophilia, and Edward Relph’s notions of place and placelessness. Three award-winning EGD projects—Borough Yards (UK), Beyond Wayfinding (USA), and Forest Net(work) (USA)—were analyzed to extract design principles applicable to rural contexts. A design-based simulation was then developed for Lefke, a culturally rich but under-communicated rural town in Northern Cyprus, to demonstrate the practical implementation of the NIE framework. Findings - The analysis shows that EGD functions both as a practical communication system and as a cultural interface. It enhances orientation and spatial clarity, reinforces local heritage and identity, and creates immersive, participatory experiences for visitors. The simulation in Lefke demonstrates that employing vernacular symbols, sustainable materials, and community-rooted narratives can transform rural environments into meaningful, experience-driven destinations.Originality/Value - This study offers one of the first structured attempts to adapt urban-derived EGD design knowledge for rural tourism development. By proposing the NIE framework and demonstrating its applicability through a design-based simulation, it provides a transferable, practice-oriented model that can guide policymakers, designers, and rural communities in shifting from passive tourism consumption to deeper, place-based engagement.